Design and Study on Square Lattice-Based Photonic Crystal Fiber with CCl4 Infiltration under Different Air Holes in the Cladding - Duc, Hoang Trong; Tran, Le Tran Bao; Thao, Tran Ngoc; Lanh, Chu Van; Thuy, Nguyen Thi (VNU Journal of Science: Natural Sciences and Technology, 2024)
In this paper, a new study is made on carbon tetrachloride (CCl 4 ) infiltrated-photonic crystal fiber (PCF) with the difference between circular air-hole in the innermost layer and others in the square lattice to improve the optical properties. Based on numerical investigation of parameters such as dispersion, effective mode area, nonlinear coefficient, and confinement loss, we obtain a variety of dispersion including all-normal and anomalous dispersion, which is as small as 0.799 ps/nm.km at 1300 nm the pump wavelength. At the same time, the highest value of nonlinear coefficient 458.718 W –1 .km –1 has been obtained, corresponding to the smallest value of 1.933 µm 2 of the effective mode area at 1550 nm of fiber Ʌ = 1.0 µm, d 1 /Ʌ = 0.8. We propose two optimal structures for directing in practical applications with supercontinuum generation (SC) in the short-wave infrared wavelength range.